If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3=-3x-(x-9)
We move all terms to the left:
-3-(-3x-(x-9))=0
We calculate terms in parentheses: -(-3x-(x-9)), so:We get rid of parentheses
-3x-(x-9)
We get rid of parentheses
-3x-x+9
We add all the numbers together, and all the variables
-4x+9
Back to the equation:
-(-4x+9)
4x-9-3=0
We add all the numbers together, and all the variables
4x-12=0
We move all terms containing x to the left, all other terms to the right
4x=12
x=12/4
x=3
| -15=2p | | 2=-17-x | | 7k-6k=8 | | b=42 | | x+1/4=-1/4(x-1) | | −6x =30 | | 2x+2(4x+8)=-4+5x | | x-11=7* | | 7-(-3y+2)=8(3y-2) | | 4x-23=-15 | | |3x-11|=7 | | 15x+9=-75 | | -3/c=-9 | | 3x+7=6x-29 | | 32+x=-44 | | 40=16-7x-15x+2 | | 4x-8(2)=24 | | 0.2x=0.25x | | 12+8=-2(7x-10) | | 20x=-(4x+16) | | (2x+53)=(x+60) | | 2x+5=222 | | f+13=-37 | | 6|5p+4|-16=20 | | 3x+7/2=5 | | -40=-2x+6 | | 13x-2=5x+11 | | 5x-14=5x+19 | | -6(x-4)-(x+3)=-42 | | 5(4x+9)=-20+5 | | 3(x+3)+1=5x-2(-3+x) | | 23x6=+(3x6) |